2021
DOI: 10.1016/j.ajem.2021.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of absolute lymphocyte count in patients with COVID-19

Abstract: Introduction Symptoms of COVID-19 vary in severity and presentation. When admitting patients to the hospital, it is desirable to isolate patients with COVID-19 from those without the disease. However, reliably identifying patients with COVID-19 in the emergency department before hospital admission is often limited by the speed and availability of testing. Previous studies determined a low lymphocyte count is commonly found in patients with COVID-19. We sought to explore the sensitivity of absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 8 publications
8
38
2
3
Order By: Relevance
“…Regardless of the viral RNA and protein presence of COVID-19 within multiple organs, inflammation has been reported to aggregate predominantly in the lungs [25] . Additionally, a reduction in ALC as an indication of leukopenia has been observed in COVID-19 patients and found to correlate with disease severity [46] . Therefore, measurement of pro-inflammatory cytokines and ALC as COVID-19 disease surrogate markers throughout injury progression in addition to lung pathology are critical components in COVID-19 patient outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Regardless of the viral RNA and protein presence of COVID-19 within multiple organs, inflammation has been reported to aggregate predominantly in the lungs [25] . Additionally, a reduction in ALC as an indication of leukopenia has been observed in COVID-19 patients and found to correlate with disease severity [46] . Therefore, measurement of pro-inflammatory cytokines and ALC as COVID-19 disease surrogate markers throughout injury progression in addition to lung pathology are critical components in COVID-19 patient outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Differentially regulated among sexes, males show higher levels of HMGB1 [39]. Another biomarker of disease severity, lymphopenia, is also more frequent in male patients [40]. Furthermore, females produce higher titres of serum IgG [41], which may help them control severe infection.…”
Section: Sex and Gender Differencesmentioning
confidence: 99%
“…Importantly, a low lymphocyte count has been proposed as a worse prognostic marker in patients with influenza virus infection [15,16], chronic obstructive pulmonary disease [17], heart diseases [18,19], and malignancy [20]. In patients infected with SARS-CoV-2, a low lymphocyte count in peripheral blood is a common clinical feature, particularly in patients with severe COVID-19 [2,21,22]. Thus far, several studies have suggested that the degree of lymphocyte count reduction correlates with illness severity in patients with COVID-19 [8,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In patients infected with SARS-CoV-2, a low lymphocyte count in peripheral blood is a common clinical feature, particularly in patients with severe COVID-19 [2,21,22]. Thus far, several studies have suggested that the degree of lymphocyte count reduction correlates with illness severity in patients with COVID-19 [8,22,23]. It remains uncertain whether a low lymphocyte count at admission in COVID-19 patients may signify a risk of subsequent adverse clinical consequences.…”
Section: Introductionmentioning
confidence: 99%